Redox-induced switch between luminescence and magnetism in a trinuclear cyanide-bridged compound. Issue 30 (11th July 2018) - Zhu, Xiao-Quan; Su, Shao-Dong; Wen, Yue-Hong; Zhang, Lin-Tao; Yang, Yu-Ying; Wu, Xin-Tao; Sheng, Tian-Lu
Abstract : A trinuclear cyanide-bridged Mn–Ru–Mn compound shows novel redox-induced transformation between luminescence and intramolecular ferromagnetic coupling. Abstract : A trinuclear cyanide-bridged luminescent compound, trans -Ru II (DMAP)4 (CN)2 [(PY5Me2 )Mn]2 [PF6 ]4 (1-R ), and its oxidation product, ferromagnetic trans -Ru III (DMAP)4 (CN)2 [(PY5Me2 )Mn]2 -[PF6 ]5 (1-O ), were synthesized and fully characterized. This is the first example of a molecular material showing a redox-controlled transformation between fluorescence and ferromagnetism.